2010
DOI: 10.1093/jac/dkp494
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid-resistant ST36 methicillin-resistant Staphylococcus aureus associated with prolonged linezolid treatment in two paediatric cystic fibrosis patients

Abstract: Linezolid resistance emerged in two isolates of ST36 MRSA colonizing the lungs of two paediatric cystic fibrosis patients. Subtherapeutic levels of linezolid may have facilitated the selection of resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 10 publications
4
38
1
3
Order By: Relevance
“…Since only three sporadic cases have been described in CF patients, data regarding clinical characteristics and risk factors associated with the development of RTIs due to LRSA isolates in this special population are lacking (15,19). In the present study, we tracked the emergence of LRSA in our institution (CFC-RBCH) and compared the clinical characteristics of CF patients with RTIs due to LRSA with the clinical characteristics of the larger group of those with RTIs due to LSSA isolates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since only three sporadic cases have been described in CF patients, data regarding clinical characteristics and risk factors associated with the development of RTIs due to LRSA isolates in this special population are lacking (15,19). In the present study, we tracked the emergence of LRSA in our institution (CFC-RBCH) and compared the clinical characteristics of CF patients with RTIs due to LRSA with the clinical characteristics of the larger group of those with RTIs due to LSSA isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Although LRSA isolates are emerging among patients undergo-ing prolonged periods of therapy (20,24,30,44,47), only three cases, one in Brazil and two in England, of infection due to resistant strains have been reported in CF patients. Both LRSA isolates identified in England were sequence type 36 (ST36), a widespread MRSA type observed in United Kingdom hospitals, whereas the type of the strain from Brazil is unknown (15,19).…”
mentioning
confidence: 99%
“…We found that linezolid was used more often in those with SCCmec type II compared to SCCmec IV, which may be reflective of these differences in antimicrobial susceptibilities. However, this antibiotic should be used with caution because resistance can emerge [33][34][35], and it may be associated with potentially irreversible side effects including peripheral neuropathy. Our study definition of exacerbations included the use of oral agents as well as IV antibiotics; this definition allowed assessment of all exacerbations and reduced the potential bias toward more severe events and only very resistant isolates, which were expected to be more frequent in SCCmec II strains.…”
Section: Discussionmentioning
confidence: 99%
“…This mutation has been reported in both staphylococci and enterococci (6,15,34,40,59,61,70,71,87,97,101), and a clear correlation between the number of mutated rRNA operons and the linezolid MIC has been found (2,35,59). Most reports of the G2576U mutation in clinical isolates are associated with some form of increased or prolonged linezolid treatment or with high linezolid usage at the local hospital (29,84), underscoring the importance of judicious use of linezolid in clinical settings. Although some studies have documented reversion of the G2576U mutation in the absence of linezolid selection (66,73).…”
Section: Resistance Caused By 23s Rrna Mutationsmentioning
confidence: 97%